EFFECT OF FOOD SHORTAGE ON GROWTH, ENERGETIC RESERVES MOBILIZATION, AND WATER QUALITY IN JUVENILES OF THE REDCLAW CRAYFISH, CHERAX QUADRICARINATUS, REARED IN GROUPS - Stumpf, Liane; Castillo Diaz, Fernando; Elizabeth Viau, Veronica; Valenti, Wagner C. [UNESP]; Lopez Greco, Laura Susana (Crustacean Soc, 2014)
The aim of this study is to analyze the impact of food shortage on growth performance, by means of energetic reserves (proteins, glycogen and lipids) mobilization and hepatopancreas cells analysis in C. quadricarinatus juveniles maintained in groups, as well as the effect on culture water quality. Two experiments were performed, each of them with two feeding regimes during 45 days. The Control feeding regime, in which crayfish were fed daily (once a day) throughout the experimental period (DF), and the Cyclic feeding regime, in which juveniles were fed for 2 or 4 days (once a day) followed by 2 or 4 days of food deprivation (2F/2D and 4F/4D, respectively) in repeated cycles. Cyclic feeding influenced growth, biochemical composition from hepatopancreas and muscle, and water quality. Juveniles cyclically fed were unable to maintain a normal growth trajectory during 45 days. Apparent feed conversion ratio, apparent protein efficiency ratio, hepatosomatic index and relative pleon mass were similar in cyclic and daily fed animals and no structural damage was found in the hepatopancreas of juveniles subjected to cyclic feeding. The novelty of this study was the significant accumulation of proteins in pleonal muscle in both cyclic feeding regimes (approx. 18%) suggesting that the storage of this constitutive material during food shortage may be an adaptation for a compensatory growth when food becomes abundant again. The cyclic feeding regimes had a positive effect on water quality decreasing inorganic nitrogen concentration. This was due to the reduction in the amount of animal excretes and feces in the group that received approx. 50% less feed. Additionally, water pH was higher in cyclic feeding tanks, as a result of lower organic matter decomposition and consequent release of CO2. Accordingly, total ammonia in the water was significantly lower for the cyclic feeding regimes compared to their respective controls. This study suggests that the protocol of cyclic feeding could be applied at least 45 days in 1 g juveniles maintained in group conditions, without affecting the energetic reserves and hepatopancreas structure, emphasizing the high tolerance of this species to food restriction.
Keywords: Cherax quadricarinatus; cyclic feeding; energetic reserves; hepatopancreas structure; water quality